A hybrid data-driven method for fast approximation of practical dynamic security region boundary of power systems. (May 2020) - Liu, Yan-Li; Shi, Xue-Jing; Xu, Yan
Highlights: A hybrid data-driven method for calculating the PDSR. A new method shows better performance on both calculation accuracy and speed. Reduce the data redundancy and computational burden by RELIEF algorithm. Develop the equivalent search space with higher search efficiency. Abstract: In the context of high-level integration of stochastic renewable energy resources such as wind and solar power, the practical dynamic security region (PDSR) with hyper-plane expression is a powerful tool for power system situational awareness and stability-constrained operation. In this paper, a hybrid data-driven method is proposed to fast approximating the PDSR boundary with hyper-plane expression. Firstly, the operating point data in the high-dimension nodal injection space is analyzed by the RELIEF algorithm to identify the key generators, active output of which has relatively great effect on transient angle stability. Then, based on the orthogonal point selection method and key generators, the equivalent search space and critical points inside it are determined with high accuracy and high speed. The hyper-plane expression of the PDSR boundary, which matches the critical points best, is finally fitted by the least square approach. Test results obtained using the IEEE 39-bus test system show the efficiency of the proposed method.